High resolution NMR studies concerning the solvation/hydration and coordination chemistry of Pt (II/IV) compounds - Westra, Arjan Nicolaas (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.